Uganda Economic Update, 10th Edition, December 2017 : Accelerating Uganda's Development, Ending Child Marriage, Educating Girls - World Bank (World Bank, Washington, DC, 2017)
Following decades of sustained economic growth during which Uganda made dramatic progresstowards poverty reduction, the country has recently experienced a period of economic growthslow down. To return to higher rates of economic growth and poverty reduction, the Government mustaddress fundamental constraints. Facing a range of internal and external shocks, Uganda's economy has grown at the average annual rate of 4.5 percent over the past five years, far lower than the historical average of about 7.8 percent. The recent deceleration in growth affected all sectors of the economy. With these lower growth rates, combined with other external shocks to the households, the remarkable progress that Uganda had made towards reducing poverty since 1992 has been reversed. In the period from 1992 to 2013, the national poverty rate declined from 56 percent to 19.7 percent. Since then, it has rebounded, increasing to a preliminary 27 percent. For Uganda to again achieve higher rates of economic growth and poverty reduction, it must address two fundamental factors: its low levels of productivity and the vulnerability if its people to poverty.